Analysis of LTE performance of V2V communications on indonesia toll road - Amrullah, Agit; Azhar, Fadhilah; Aminuddin, Afrig; Ernawan, Ferda; Elhadi, Haitham (Institute of Electrical and Electronics Engineers Inc., 2023)
Vehicle-to-vehicle (V2V) is a transportation technology that uses wireless communication developed to solve transportation problems. In carrying out V2V communication, it has developed from the 802.11p ad-hoc communication protocol or what is known as Vehicular Ad-hoc Network (VANET) to Long Term Evolution (LTE). LTE performance, with data transmission speed on the download line of 150 Mbps and upload of 75 Mbps, gives an advantage over VANET on the communication line. However, the performance of LTE at data transmission speeds with vehicle speeds on freeways when applied in Indonesia with vehicle speeds between 60 km/h and a maximum of 100 km/h provides a different scenario from vehicles in cities with speeds of only 30 km/h up to 50 km/h. In this study, an analysis of V2V communication performance on LTE networks using Omnet+ + will be carried out on freeways in Indonesia. From the results obtained for packages of 100,200 and 300 Bytes and speeds of 60 km/h to 100 km/h, the average delay is 0.00037 ms, and the average throughput is 0.00018797466667 bps.